PELATIHAN E-COMMERCE DAN MEMBUAT TOKO ONLINE PADA ASRAMA YATIM DAN DHUAFA AL ALIF 165 - Ahmad Jurnaidi Wahidin; Tiska Pattiasina; Dudi Duta Akbar; Pungkas Budiyono (PEMANAS: Jurnal Pengabdian Masyarakat Nasional, 2021)
The COVID-19 pandemic which was designated as a national disaster on March 14, 2020 made many sectors and lines of life weakened including trade, one of which was affected was the Asrama Yatim and Dhuafa Al Alif 165 Pondok Rajeg, Cibinong, Bogor Regency, this dormitory has trading activities such as selling cassava chips, pastries and work on trellis orders, but the sales process is still done manually, which is only trading on the side of the road in front of the hostel. The existence of a pandemic plus government regulations regarding PPKM greatly affected the mobility of the community, including in the dormitory area, so that there were very few buyers which caused the income of the Asrama Yatim and Dhuafa Al Alif 165 to decrease. By holding one-day training online with the theme of e-commerce and making a shop on the shopee application, foster children and hostel administrators can expand the market with a global reach and can transact in cyberspace without being hindered by location and conditions. This activity has made a positive contribution, namely increasing knowledge and expertise in the field of information technology in order to increase product sales. New knowledge about selling products using shopee. The training participants already know and practice how to create a shop, upload products, determine product categories to determine store locations and delivery services on shopee. Furthermore, training with the same theme can be given again but using a different marketplace such as Tokopedia, Lazada, Bibli and others.